Thomas Kinkade's Cape Light : On Christmas Eve - Book 11 - Kinkade, Thomas 1958-; Spencer, Katherine 1955- (New York : Berkley Books, 2010)
Despite her frayed relationship with Charlie, Lucy takes in a runaway teenager, a decision that Charlie is none too pleased with; meanwhile, Betty falls in love with a struggling writer who is moonlighting as Santa Claus.
"A Parachute Press book."
Keywords: Cape Light (Imaginary place) -- Fiction; City and town life -- Fiction -- New England; Christmas -- Fiction; New England -- Fiction